2007
DOI: 10.1029/2005jb004134
|View full text |Cite
|
Sign up to set email alerts
|

Plastic flow of two‐phase marbles

Abstract: [1] To quantify the effect of rigid inclusions on the flow behavior of a creeping matrix, we fabricated a suite of two-phase marbles by hot isostatically pressing mixtures of calcite and quartz powders and subsequently deformed these synthetic rocks at 300 MPa confining pressure, up to 100 MPa pore pressure, temperatures ranging from 873 to 1073 K, strain rates and stresses ranging from $10 À7 s À1 to $10 À3 s À1 and $4 MPa to 190 MPa, respectively. In constant displacement rate tests performed to axial strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 82 publications
(112 reference statements)
1
15
0
Order By: Relevance
“…This is in agreement with previously conducted experimental studies (Wilson, 1984;Tullis and Wenk, 1994;Austin et al, 2014). In natural shear zones, GBS accompanied by diffusion creep or dislocation glide is often proposed as a process responsible for the weaker CPO in polymineralic rocks, compared to their monomineralic counterparts (e.g., Krabbendam et al, 2003;Song and Ree, 2007). A relationship between CPO and GBS activity is complex (e.g., compare: Fliervoet et al, 1997;Dimanov et al, 2007).…”
Section: Effect Of Second Phase On Deformation Mechanisms and Cpo Devsupporting
confidence: 73%
“…This is in agreement with previously conducted experimental studies (Wilson, 1984;Tullis and Wenk, 1994;Austin et al, 2014). In natural shear zones, GBS accompanied by diffusion creep or dislocation glide is often proposed as a process responsible for the weaker CPO in polymineralic rocks, compared to their monomineralic counterparts (e.g., Krabbendam et al, 2003;Song and Ree, 2007). A relationship between CPO and GBS activity is complex (e.g., compare: Fliervoet et al, 1997;Dimanov et al, 2007).…”
Section: Effect Of Second Phase On Deformation Mechanisms and Cpo Devsupporting
confidence: 73%
“…It has since been established experimentally that carbonate rocks become ductile under relatively low confining pressures. Under stress, the depth of brittle-ductile transition in these rocks will depend on the grain size, porosity, content and connectivity of non-carbonate material, availability of fluids, and temperature (De Bresser et al 2005;Paterson and Wong 2005;Renner et al 2007;and references therein), and can be as shallow as~1 km for a pure material (Fredrich et al 1989). A confining P of 0.5 kbar is typically cited for the reference Carrara marble (Schubnel et al 2006), which is closely similar to fine-grained anchimonomineralic (~98 % pure, with a mean grain size of 0.15 mm) calcite carbonatites.…”
Section: Textural Record Of Deformation In Carbonatitesmentioning
confidence: 99%
“…Experimental studies have shown that the addition of as little as 5 vol% uniformly dispersed quartz to fine-grained calcite aggregates increases the strength of the material (Dresen et al 1998;rybacki et al 2003;Xiao & Evans 2003;renner et al 2007). However, it is difficult to envision this strength variation resulting in contemporaneous stress variations across the shear zone, when quartz-rich limestones (Gault) are juxtaposed with pure limestones (Urgonian).…”
Section: Diffusion Creepmentioning
confidence: 99%